An Empirical Analysis of Mexican Merger Policy - Avalos, Marcos (2012)
A newly created dataset including 239 decisions made by the Mexican Federal Competition Commission on horizontal mergers is used to estimate the different factors affecting the Commission's resolution decisions. The decision-making process has been approximated by two different discrete choice models. Our results indicate that, contrary to the Commission's objective, the presence of efficiency gains increases the probability of a case being challenged. We also find that factors different from the ones explicitly mentioned by the Commission have a significant effect upon the Commission's final decision. In particular, the presence of a foreign company among the would-be merger firms significantly increases the likelihood of observing an allowed merger.